Phương pháp chiếu lặp giải phương trình tích phân kỳ dị Fredholm loại III - Quảng, Lê Xuân (Journal of Computer Science and Cybernetics, 2016)
In this paper the iterative-projection method for solving the Fredholm singular  integral equation of the first kind Ax(t),   where K(t,s), y(t) are given functions of the space C0[-1,1] and C0[-1,1] ´ [-1,1], respectively. The method is convergent with the rate of power.